Urgensi Kecakapan Literasi Bahasa Indonesia di Sekolah: Perspektif Kesalahan Berbahasa Pada Buku Pendukung Pembelajaran - Nira Kusumawati; Annisa Rizki Fadilla (Balai Bahasa Sulawesi Selatan, 2024)
This paper aims to show the urgency of Indonesian language literacy skills in schools from the perspective of the decadence of linguistics rules in learning support books. Analysis using qualitative methods. Data analysis was carried out descriptively. This type of research is content analysis with data sources in the form of three Indonesian language e-modules (elementary, junior high, and high school) which were determined by purposive sampling. The basic data collection use tapping technique and the advanced technique use taking notes. The validity of the data was carried out by testing referential validity and intrarater reliability. The analysis shows that there are language errors in school learning support books (elementary, junior high, and high school). The number of spelling mistakes found in learning support books made by teachers (even Indonesian language teachers) is one indicator that in terms of Indonesian literacy skills at school, teachers still put aside linguistic rules. The existence of these errors is a manifestation of the urgency of Indonesian literacy skills in schools. AbstrakArtikel ini bertujuan melihat urgensi kecakapan literasi bahasa Indonesia di sekolah dari perspektif kesalahan kaidah kebahasaan dalam buku pendukung pembelajaran. Analisis penelitian memakai metode kualitatif. Analisis data dilakukan secara deskriptif. Jenis penelitian ini adalah analisis konten (content analysis) dengan sumber data berupa tiga e-modul Bahasa Indonesia (SD, SMP, SMA) yang ditentukan dengan purposive sampling. Teknik pengumpulan data dilakukan dengan teknik dasar sadap serta teknik lanjutan berupa catat. Keabsahan data menggunakan uji validitas referensial dan reliabilitas intrarater. Hasil analisis menunjukkan ada kesalahan berbahasa pada buku pendukung pembelajaran sekolah (SD, SMP, dan SMA). Banyaknya kesalahan ejaan yang ditemukan dalam buku pendukung pembelajaran yang dibuat oleh guru (sekalipun guru Bahasa Indonesia) menjadi salah satu indikator bahwa dalam ihwal kecakapan literasi bahasa Indonesia di sekolah, guru masih mengesampingkan kaidah kebahasaan. Adanya kesalahan tersebut sebagai wujud urgensi kecakapan literasi bahasa Indonesia di sekolah.